Construction of Sensitive Surface‐Enhanced Raman Spectroscopy Chip with Sub‐Nanometer WO3−x Nanowire‐Based Superstructures for Multicomponent Detection. Issue 9 (7th August 2019) - Ye, Yuting; Bai, Hua; Li, Mengchen; Tian, Zheng; Du, Ruifeng; Fan, Wenhao; Xi, Guangcheng
Abstract: Exploring nonmetallic plasmonic materials is desirable yet challenging. For a long time, free‐plasmonic semiconductor is difficult to be used in high‐sensitive surface‐enhanced Raman spectrum (SERS) due to poor enhanced factor and high‐fluorescent background. Herein, it is reported that a nonmetallic plasmonic SERS chip, constructed with a highly ordered sub 1 nm WO3− x nanowire‐based superstructure, shows multicomponent detection capability. The densely arranged nanowires enable a strong localized surface plasmon resonance due to the high charge carriers' density induced by oxygen vacancies in the nanowires. In addition to the usual charge‐transfer enhancement, such nonmetallic WO3− x displays a unusual dramatic plasmon‐enhanced SERS sensing performance with a detection limit of 10 −10 m and a maximum Raman enhanced factor of 8.3 × 10 7 . The substrate fluorescence signals are efficiently quenched, making the SERS spectra more distinguishable. More importantly, the prepared WO3− x SERS chip through micro–nano printing realizes the separation and detection of multicomponents simultaneously. Abstract : A nonmetallic plasmonic surface‐enhanced Raman spectrum (SERS) chip, constructed with a highly ordered sub 1 nm WO3− x nanowire‐based superstructure, shows multicomponent detection capability. Such nonmetallic WO3− x displays a unusual dramatic plasmon‐enhanced SERS sensing performance with an ultrasensitive detection limit of 10 −10 m and a maximum Raman enhanced factor of 8.3 × 10 7 .